Peningkatan Motivasi dan Hasil Belajar Siswa pada Pembelajaran Lingkaran dengan Metode Penemuan Terbimbing - Suharto (Cakrawala: Jurnal Pendidikan, 2017)
This research was a classroom action research aimed to determine the improvement of motivation and learning achievement of subject matter of the circle and teacher performance with guided discovery method. The subjects of the study were VIII D students at SMP Negeri1 Talang Tegal Regency of 2015/2016 consisted of 32 students and 2 mathematics teacher’s. There were two cycles; each cycle consisted of four stages of planning, implementation, observation and reflection. The results in the first cycle obtained the average value of student learning outcomes 71.86 with the lowest score of 50 and the highest score of 90.00 and students obtained a minimum score of 75 were 14 students (43.75%). While in the second cycle obtained an average score of 79.7 with the lowest score of 50 and the highest value of 100 and students received a minimum score of 75 were 27 students (84.4%). The result of teacher's observation on teacher I cycle has not been effective yet, teacher performance percentage was 80,9%. However in cycle II the teacher showed an increase to 90.6%. Student activity in cycle I was 51.5%, while in cycle II rose to 87,5%. This study proved that guided discovery method can improve the motivation, learning achievement and teacher performance